Students' Motivation In Following Badminton Extracurricular Activites At SMAN 3 Ponorogo - Candramaya, Delvi Cintanthya; Wijaya, Andhega (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
The purpose of this study was to determine students' motivation in participating in badminton extracurricular activities at SMAN 3 Ponorogo in the 2023/2024 academic year. This descriptive study used an instrument in the form of a questionnaire made in the form of a google form, and 30 students who participated in badminton extracurricular activities were present in this study. The location of the study was carried out at the Surya Mas Ponorogo Badminton Sports Building located on Jl. Pramuka Gg. III No.13, Ronowijayan, Siman District, Ponorogo Regency, East Java 63471. The reliability test produced a value of 0.869, while its validity was marked with a value of 13. The results of the calculation through quantitative descriptive analysis found an increase in student motivation in participating in badminton extracurricular activities at SMAN 3 Ponorogo, namely 100%. From here, it can be seen that the level of student motivation in participating in badminton extracurricular activities is very high. These findings can help students to know their motivation and help extracurricular coaches in improving the factors that encourage the success of badminton extracurricular activities at SMAN 3 Ponorogo.